Six Strategies for Optimizing Linear Growth through Improving Awareness of Breastfeeding, Dietary Diversity in Complementary Feeding, and Growth Monitoring during Early Life - Muhammad Yazid, Jalaludin; Poh, Bee Koon; John, Collins; Suryawan, Ahmad; Zalilah, Mohd Shariff; Cheang, Hon Kit; Ng, Alvin Lai Oon *; Sri Wahyu, Taher; Lee, Shoo Thien; Adedeji, Idris Abiodun; Eberechi, Oyenusi Elizabeth; Michael, Godpower Chinedu; et al. (JournalGURUS, 2023)
Only one-fourth of the countries under the Sustainable Development Goal are ‘on track’ to reduce the burden of malnutrition as of 2020. A deficit in linear growth during the first 5 years of life is mainly due to growth faltering in the first 1000 days. This deficit has been consistently reported to be linked to suboptimal cognitive neurodevelopment, while its improvement in early childhood has been reported to offer an opportunity for rescuing neurocognitive potential. This paper describes the perspectives of multidisciplinary experts, representing a range of disciplines related to child growth and nutrition, from Nigeria, Indonesia, and Malaysia, who convened virtually to review and discuss measures aimed at preventing a further increase in growth faltering, including stunting, among children aged 0-3 years under the current prevailing circumstances. Based on the latest evidence of practices and knowledge, the expert panel proposed six strategies to support linear growth in early life which consists of 2 new initiatives: 1) increasing peer-to-peer knowledge transfer among HCP via digital engagement; 2) increasing knowledge transfer from HCPs to caregivers via social media; while maintaining the existing strategies: 1) stimulating initiatives to support breastfeeding during the first 6 months of life; 2) improving quality of complementary feeding; 3) strengthening growth monitoring to detect suboptimal growth in early childhood; 4) optimizing public-private engagement. The recommended solutions presented herein are the culmination of the collective insights of the expert panel. These recommendations offer invaluable approaches on addressing the critical public health issue of malnutrition, specifically growth faltering, and can benefit not only the three countries concerned but also other low and middle-income countries facing similar nutritional challenges.